Cross-sectional exercise-related differences in PTSD symptoms, psychological distress, physical pain, and sleep quality in trauma-exposed adults - Nicholas J. SantaBarbara; Nicholas J. SantaBarbara; Erica R. Checko; Erica R. Checko; Michelle M. Pebole; James W. Whitworth; James W. Whitworth; James W. Whitworth; James W. Whitworth (Frontiers in Psychology)
PurposePsychological trauma can lead to PTSD which is associated with numerous negative health outcomes. Exercise has beneficial effects on PTSD; however, the amount of exercise associated with these benefits remains unknown. To examine self-reported exercise-related differences in PTSD symptom severity, psychological distress, pain, and sleep quality in a national sample of trauma-exposed adults.MethodsParticipants completed online assessments of exercise participation, PTSD symptom severity, psychological distress, pain, and sleep quality. Exercise level was defined as Active (≥24 on the Godin-Leisure Time Exercise Questionnaire [GLTEQ]), Insufficiently Active (1–23 on the GLTEQ), or Inactive (no reported exercise). MANCOVA was used to determine the relationship between exercise level (i.e., independent variable) and all outcomes (PTSD, distress, pain, sleep) with post hoc means comparison adjusted for age.ResultsParticipants’ (n = 500) mean age was 34.9 ± 13.0, and 68% were female. The overall model for exercise was significant, such that Active participants reported less PTSD symptom severity, psychological distress, and pain, and better sleep quality than Inactive participants.ConclusionMeeting the recommended amount of weekly physical activity with moderate-to-vigorous exercise is associated with better physical and mental health among trauma survivors. Longitudinal research is needed to confirm these cross-sectional findings.